Owner Situationally Specific Motivation, And Organisational Citizenship Behaviour: A Study of New Zealand Entrepreneurs - Saifon Chairungruang (Universitas Pelita Harapan, 2016)
Despite the extensive developments in entrepreneurship theory over recent decades, there is a lack of empirical studies examining the influence of owner situationally specific motivation on firm performance focusing on small and medium sized enterprises (SME) in New Zealand. The present study attempts to bridge this gap. At the same time, it responds to calls to extend performance measures to include non-financial outcomes by using organisational citizenship behaviours – OCB – as a performance measure. This is based on the observation that OCBs are consistently presented in the literature as a cornerstone of good performance and competitive advantage. The study uses mixed methods, combining surveys and semi-structured interviews. Multiple regression is used to analyse data on entrepreneurial situationally specific motivation (i.e. communicated vision, self-efficacy, and goals) provided by a sample of 107 firms. In addition, 107 pairs, each comprising an owner-manager plus a random employee from the same firm, also supplied data on organisational citizenship behaviours. Finally, nine qualitative interviews were conducted with owners to further enhance understanding. The study highlights the statistical significance of the positive relationship of entrepreneurial situationally specific motivation and OCB. This finding suggests that owners who have confidence in their abilities [self-efficacy] and who have communicated their vision [communicated vision] are more likely to encourage in their employees the behaviours that are required in order to function well in their organisations. The implications of this finding for potential future research are discussed.